The Role of Work Engagement in Mediating the Effects of Leadership and Competence on Employee Performance at the Medan Barat District Office - Fatimah Hia, Siti; Anwar, Yohny; Rahayu, Sri (International Conference Epicentrum of Economic Global Framework, 2026)
This study aims to examine and analyze the role of work engagement in mediating the effects of leadership and competence on employee performance at the Medan Barat Subdistrict Office. The study employed a quantitative approach with a population of 60 civil servants at the Medan Barat Subdistrict Office. A saturation sampling technique was used, meaning the entire population was included as the study sample. Primary data were collected through a questionnaire and analyzed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method with the assistance of the SmartPLS software. The results indicate that leadership has a positive and significant effect on employee performance and work engagement. Competence also has a positive and significant effect on employee performance and work engagement. Furthermore, work engagement has a positive and significant effect on employee performance. The results of the indirect effect test indicate that work engagement mediates the effect of leadership on employee performance and mediates the effect of competence on employee performance. The R-squared value for work engagement of 0.302 indicates that leadership and competence explain 30.2% of work engagement. Meanwhile, the R-squared value for employee performance of 0.518 indicates that leadership, competence, and job engagement account for 51.8% of the variance in employee performance. Based on the research findings, it can be concluded that leadership and competence enhance employee performance, both directly and through job engagement. Job engagement acts as a partial mediator in these relationships.